(خصوصية النراضي في العقد الإلكتروني قانون المعاملات الإلكترونية (سلطنة عمان أنموذجا - Salim Musallam Ahmed Al Massheni
The subject being discussed in this study is the Confidentiality of Mutual Consent in e-contracts. Its importance emerges from the fact the confidentiality of electronic contracts should be considered when teaching this subject. The regulations of such issues do not match those of the general implications of the contract provisions. As a result, a number of legal problems come out while trying to bring into force the provisions of the contract theory. The researcher, hence, aims at highlighting the confidentiality of the electronic agreements in order to show how huge the problem is, and he tries to pinpoint the statutory breach when implementing the general theory of the contract over the confidentiality of electronic agreements. Then, he proposes the appropriate solutions for those problems. The Omani Law of Electronic Transaction has been deemed a case study in order to dig deeply in its contents and find out the confidentiality aspect of the law. On the other hand, the study tries to highlight the weakness and strengths when addressing the confidentiality issue of the electronic agreements. The researcher has used the inductive analytical approach by extrapolating and tracing details related to confidentiality of electronic contracts, studying and deliberating them in order to reach the goal of the study, i.e. highlighting the problems resulting from the confidentiality of contracts, and the given proper solutions. Tackling the subject, the researcher has been able to prove the correctness of the hypothesis which is that confidentiality encompasses some issues of the electronic agreements, and those issues do not go in line with those of the general rules of the contract theory. Therefore, they need special legislative regulations. The study showed inadequacy of the Omani Law of Electronic Transactions in dealing with the confidential issues. The law focused on proof wise issue while ignoring many other such as compromise aspects. The study also showed the constraints/ short range of the jurisprudence academies in keeping pace with the technical developments in progress. The fatwas (formal legal opinions) have been deemed obsolete when compared with the rapid evolution of the electronic fields which might cause changes in the jurisdiction of any issue. The study also showed that the will of the electronic document will be subjected to drawbacks that will require enforcement of law and will in order to protect and satisfy the formal requirements of a signed writing.